Motivational Orientation towards Learning English: The Case of Indonesian Undergraduate Students at University Utara Malaysia (UUM) - Ismail Ismail (Journal of English Language Teaching and Literature (JELTL), 2022)
Realizing motivation is a part of the key aspects in effective English learning as a EFL in Indonesia, there have been many scholars investigating the motivation of Indonesian university students who major in English studies. However, Empirical researches discussing motivation toward learning English of Indonesian students studying abroad from different disciplines are uncommon. Employing Gardner's instrumental and integrative motivation, this research aims to examine the major motivational level toward Learning English of Indonesian undergraduate students who are studying at the University Utara Malaysia (UUM). 20 items of a questionnaire were administered to 89 students from different disciplines. This study reported that the students were highly motivated both in integrative and instrumental motivation. However, they had more integrative motivation than instrumental motivation. In terms of integrative motivation, students learned English because they believe that it can give them the chance to interact with a diverse range of individuals. However, in terms of instrumental motivation, students much concentrate to learn English for their long-term objectives, such as succeeding in their careers and jobs.